Dog population management in Malawi and Peru - Åsbjer, Elina (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2009)
The aim of the study was to look into the implementation of guidelines of dog population management (DPM), published by WHO & WSPA, ICAM-coalition and OIE, in Malawi and Peru. Fieldstudies with interviews with representatives of authorities, international organizations and local NGOs were conducted in these two countries. The conclusions from the inteviews were that guidelines are only partially implemented in both countries, but the problems differ in between. No comprehensive national plan for DPM exist in either country and there are no executive group taking full responsibility. In Malawi a NGO have taken the responsibilty to try to pilot a program and involve authorities to coordinate and harmonize there work. However, lack of information about the dog population and the rabies situation as well as lack of resources, makes it very difficult to succeed with DPM. Insufficient information also makes it difficult to evaluate any rabies vaccination program. In Peru on the other hand, they have good knowledge about the number of dogs and have also succeeded very well in rabies control. Even if they lack an executive working group, they have a legisltaion supporting DPM and a direction working with eg. education programs for children. They have a comprehensive rabies program which shows that rabies control is indeed possible but instead they have other problems with diseases as echinococcosis. In both countries reproduction control is totally dependent on the work done by NGOs. The need is overwhelming and cost-benefit analysis very important when resources are limited.